Kinect as an access device for people with cerebral palsy: A preliminary study - Cabrera, Rafael; Molina, Alberto; Gómez, Isabel; García-Heras, Joaquín (International journal of human-computer studies, 2017)
•We look at the potential of the Kinect sensor as an access device for people with involuntary movements.•We develop a speed-based algorithm to transform Kinect data into discrete events.•We assess the behavior of when is used by people with cerebral palsy and involuntary movements as an access devices.•Kinect filter some of the involuntary movements of people with involuntary movements. Cerebral palsy (CP) describes a group of disorders affecting the development of movement and posture, causing activity limitation. Access to technology can alleviate some of these limitations. Many studies have used vision-based movement capture systems to overcome problems related to discomfort and fear of wearing devices. In contrast, there has been no research assessing the behavior of vision-based movement capture systems in people with involuntary movements. In this paper, we look at the potential of the Kinect sensor as an assistive technology for people with cerebral palsy. We developed a serious game, called KiSens Números, to study the behavior of Kinect in this context and eighteen subjects with cerebral palsy used it to complete a set of sessions. The results of the experiments show that Kinect filters some of peoples involuntary movements, confirming the potential of Kinect as an assistive technology for people with motor disabilities.